2013
DOI: 10.1016/j.bbr.2013.02.036
|View full text |Cite
|
Sign up to set email alerts
|

VEGF reverts the cognitive impairment induced by a focal traumatic brain injury during the development of rats raised under environmental enrichment

Abstract: The role of VEGF in the nervous system is extensive; apart from its angiogenic effect, VEGF has been described as a neuroprotective, neurotrophic and neurogenic molecule. Similar effects have been described for enriched environment (EE). Moreover, both VEGF and EE have been related to improved spatial memory. Our aim was to investigate the neurovascular and cognitive effects of intracerebrallyadministered VEGF and enriched environment during the critical period of the rat visual cortex development. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 65 publications
0
18
1
Order By: Relevance
“…Our study shows that this effect can be partially reverted by a compensatory mechanism stimulating other areas such as the somatosensory and the motor cortices but, for a full recovery, a combination of both these strategies; i.e., environmental enrichment (somatosensorial implementation) and exercise (motor implementation), is required. Indeed, neither our previous results with cognitive enrichment (Argandoña et al, 2009;Ortuzar et al, 2013) nor our current results with physical enrichment are able to reach a reversion as deep as the one we attained with the combination (Argandoña et al, 2009). These results stand in accordance with a previous study on the hippocampus describing additive effects on adult neurogenesis of both components of the environmental enrichment (Fabel et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study shows that this effect can be partially reverted by a compensatory mechanism stimulating other areas such as the somatosensory and the motor cortices but, for a full recovery, a combination of both these strategies; i.e., environmental enrichment (somatosensorial implementation) and exercise (motor implementation), is required. Indeed, neither our previous results with cognitive enrichment (Argandoña et al, 2009;Ortuzar et al, 2013) nor our current results with physical enrichment are able to reach a reversion as deep as the one we attained with the combination (Argandoña et al, 2009). These results stand in accordance with a previous study on the hippocampus describing additive effects on adult neurogenesis of both components of the environmental enrichment (Fabel et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Such structural changes may lead to EE-enabled compensation and recovery of function after injury (Rose et al, 1987; Kolb and Gibb, 1991; Whishaw et al, 1991; Passineau et al, 2001; Will et al, 2004). Under uninjured conditions, EE-induced structural changes are thought to occur due to upregulation of trophic factors such as VEGF and BDNF which promote cell survival and plasticity, and an increase in activation of transcription factors of proteins mediating plasticity (Young et al, 1999; Rampon et al, 2000; Keyvani et al, 2004; Will et al, 2004; Gaulke et al, 2005; Hoffman et al, 2008; Sozda et al, 2010; Monaco et al, 2013; Ortuzar et al, 2013). Interestingly, studies have reported an increase in BDNF expression after TBI (Hicks et al, 1997; Chen et al, 2005), with no further increase following exposure to EE (Chen et al, 2005) suggesting that EE-induced benefits for recovery after TBI may not depend on increasing the levels of trophic factors.…”
Section: Mechanisms Promoting Improved Behavioral and Pathological Rementioning
confidence: 99%
“…Dysregulation of VEGF signaling has been implicated in several neuropathological conditions such as stroke, amyotrophic lateral sclerosis (ALS), depression and Alzheimer's disease (Carmeliet and Storkebaum, 2002;Quaegebeur et al, 2011;Warner-Schmidt and Duman, 2008). Remarkably, restoring or enhancing VEGF signaling can improve learning and memory in healthy and brain injured animals (Cao et al, 2004;Ortuzar et al, 2013) and protect the brain from damage and dysfunction caused by stroke or ALS (Jin et al, 2000;Storkebaum et al, 2005;Zhang and Chopp, 2009). Despite increasing evidence that diabetes leads to abnormal VEGF signaling and pathogenic vessel remodeling (Caldwell et al, 2005;Prakash et al, 2012;Reeson et al, 2015), no study has explored whether manipulating VEGF signaling in an animal model of diabetes could have therapeutic value in preventing pathological changes to cognition.…”
Section: Introductionmentioning
confidence: 99%